ANALISIS EFEKTIVITAS KINERJA RIPPLE MILL MENGGUNAKAN OVERALL EQUIPMENT EFFECTIVENESS: STUDI DI PALM OIL INDUSTRY SUMATERA UTARA - Amelia, Putri; Lubis, Rizki Fadhillah (Politeknik ATI Padang, 2022)
One of the factors that can affect the production process on the palm oil industry production floor is the decreasing effectiveness of the performance of production machines, including ripple mills. This study aims to analyze the effectiveness of ripple mill performance using Overall Equipment Effectiveness. This method uses three basic ratios: availability ratio, performance ratio, and quality ratio. The results of this study indicate that the Overall Equipment Effectiveness value obtained on the ripple mill machine in one of the palm oil industries in North Sumatra is still below 41.45% while the international OEE standard is 85%. The damage that is often encountered is a decrease in machine speed and rotor wear so that the rotor plate is blunt and causes ineffective breaking.